Antimicrobial peptides could antagonize uncontrolled inflammation via Toll-like 4 receptor - Buccini, Danieli F.; Roriz, Beatriz C.; Rodrigues, Júlia M.; Franco, Octavio L. (Frontiers in Bioengineering and Biotechnology, 2022)
Antimicrobial peptides are part of the organism’s defense system. They are multifunctional molecules capable of modulating the host's immune system and recognizing molecules present in pathogens such as lipopolysaccharides (LPSs). LPSs are recognized by molecular patterns associated with pathogens known as Toll-like receptors (TLRs) that protect the organism from pathological microorganisms. TLR4 is responsible for LPS recognition, thus inducing an innate immune response. TLR4 hyperstimulation induces the uncontrolled inflammatory process that is observed in many illnesses, including neurodegenerative, autoimmune and psoriasis). Molecules that act on TLR4 can antagonize the exacerbated inflammatory process. In this context, AMPs are promising molecules capable of mediating toll-like receptor signaling. Therefore, here we address the AMPs studied so far with the aim of inhibiting the intense inflammatory process. In addition, we aim to explore some of the interactions between exogenous AMPs and TLR4.